2021
DOI: 10.1177/01454455211033515
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Occupational Health in Military Firefighters: An Understudied Population

Abstract: To our knowledge, no studies on health conditions in U.S. military firefighters exist. Data and demographics from the Defense Medical Epidemiology Database were analyzed on several shared medical issues among military personnel and civilian firefighters. Descriptive statistics and Chi-Square goodness of fit tests were conducted to support study aims. Between 2001 and 2015, substantial incidence rate increases (per 10,000) of tinnitus, PTSD, insomnia, and OSA (2005–2015) were observed. Modest to large increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Exposure to traumatic events is associated with the development of both psychopathologies addressed in this study, PTSD and SSD [4,6,23], which is why firefighters are seen as a high-risk group for the development of these conditions. Firefighting is a stressful occupation that exposes individuals to occupational stressors, poor sleep, and extreme and tragic events.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Exposure to traumatic events is associated with the development of both psychopathologies addressed in this study, PTSD and SSD [4,6,23], which is why firefighters are seen as a high-risk group for the development of these conditions. Firefighting is a stressful occupation that exposes individuals to occupational stressors, poor sleep, and extreme and tragic events.…”
Section: Discussionmentioning
confidence: 86%
“…This instrument, which is a 3-point Likert scale, assesses the presence and severity of somatic symptoms. Total symptom severity score is obtained by summing the score for each of the 15 items, and range from 0 to 30, with severity classified as no-minimum (0-4); low (5-9); medium (10)(11)(12)(13)(14)(15) and high (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). PHQ-15 is considered reliable and valid for general and clinical populations (Cronbach's α = 0.80) [15,16].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the risk factors for cardiovascular disease are broad and are likely to be more evenly distributed among multiple occupational groups. Although studying a different population of firefighters, the military firefighters researchers also found that, from 2001 to 2015, incident rates of alcohol use disorder, hypertension, and tobacco use all declined 19 . These findings are likely due to improved treatment and screening procedures, as well as larger shifts in social attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent investigation into changes in military firefighters' reported medical and mental health conditions over time found significant increases in both tinnitus and mental health conditions between 2001 and 2015 19 . Importantly, researchers found that incidence rate of tinnitus more than quadrupled during the study period (reaching 60 cases per 10,000 individuals in 2015) and that the incidence rates of mental health conditions including depression, generalized anxiety disorder, insomnia, and adjustment disorder also saw moderate to significant growth 19 . For this at-risk group, exploring how job stress may heighten the risk for adverse health outcomes such as tinnitus might offer insight into what mitigation strategies will be the highest yield for occupational health providers and other advocates.…”
mentioning
confidence: 99%
See 1 more Smart Citation